Effect of a resonant suspended ceiling on the acoustic properties of a hall/Rezonansinių kabamųjų lubų įtaka salės akustiniams rodikliams - Vytautas Stauskis (Journal of Civil Engineering and Management, 1996)
The article covers the experimental research into basic acoustic properties of a hall using a new type resonant suspended ceiling with large area cross-shaped apertures between surfaces.